Socialization of Economic and Islamic Financial Sustainability for Student Entrepreneurs in Kota Kinabalu, Sabah, Malaysia - Riyaldi, Muhammad Haris; Halim, Hendra; Nurdin, Ridwan; Budin, Dg Safrina Ag; Nizam, Ahmad; Abd Karim, Mohd Rahimie bin; Lada, Suddin; Amri (PT FORMOSA CENDEKIA GLOBAL, 2024)
The